The Impact of Group Psychotherapy on the Mental Health of Servicemen with Post-Traumatic Stress Disorder. - Собкова, Світлана; Мотозюк, Людмила; Чорна, Наталія; Власов, Володимир (Lifescience Global, 2024)
Being in a combat zone negatively affects the psycho-emotional state of servicemen, which can lead to post traumatic stress disorder (PTSD). The purpose of the study is to determine whether group psychotherapy is effective in reducing symptoms of post-traumatic stress disorder in military personnel. The research methodology is presented by the Post-Traumatic Stress Disorder Checklist for DSM-5, the World Health Organization Quality of Life Instrument, and statistical methods (ANOVA, Levene’s test, and the Mann-Whitney U-test). The results showed that group therapy effectively reduced symptoms of posttraumatic stress disorder from 42.5 (SD = 6.1) to 31.2 (SD = 5.7). The practical significance of the results obtained lies in the possibility of their use in the treatment of post-traumatic stress disorder in military personnel. Prospects for further research lie in studying effective methods of treating other mental disorders in people affected by war.
International Journal of Statistics in Medical Research
Keywords: Post-traumatic stress disorder, group psychotherapy, servicemen, therapy effectiveness, therapeutic progress, mental health, trauma, psychological rehabilitation